An introduction to sociology - Murji, Karim; Neal, Sarah; Solomos, John (SAGE, 2022)
"An introductory guide to the key concepts, themes, and topics in the discipline of sociology, providing sociology students with comprehensive coverage of all the main areas of study for their first year and beyond"--Provided by publisher.